(untitled) (CIPEEX, 2025)
Beta thalassemia major is a rare hereditary disease that causes severe anemia, treated with blood transfusions and iron chelation. People with sickle cell disease can experience significant symptoms and complications. This study aims to report two cases of adolescents with beta thalassemia major and unplanned pregnancies. This is a narrative literature review, with articles selected from 2020 to 2024. Results and discussion: One patient had worsening anemia, increased need for transfusions and fetal complications. The other had hypothyroidism and serious complications such as hemorrhagic shock and respiratory infection. Both required postpartum transfusions and chose medroxyprogesterone as their contraceptive method. The report highlights the need for contraceptive guidance and specialized prenatal care in collaboration with hematologists. Thalassemias are a group of inherited blood disorders, the deletion of three α-globin genes results in hemoglobin H (Hb H) disease. Ovulation induction is associated with the risk of ovarian hyperstimulation syndrome, which is characterized by increased vascular permeability and has abnormalities of renal function, among others. Pregnant women with thalassemia show that many dozens of them received desferrioxamine throughout pregnancy with no evidence of a toxic or teratogenic effect, although it increases the risk of thrombosis three to four times. According to most studies on pregnant women with thalassemia intermedia, 60-80% of patients need transfusions during pregnancy. However, pregnancy with thalassemia should be considered high-risk and should always be preceded by a full pre-conception assessment. In conclusion, sickle cell disease is a risk factor for morbidity/mortality and adverse perinatal outcomes, affecting the health of pregnant women, the fetus and the newborn.Keywords: Thalassemia; Pregnant women; Hemoglobin; Beta thalassemia.BibliographyTrigo, L. A. M. C., Surita, F. G., Parpinelli, M. A., Pereira, B. G., Fertrin, K. Y., amp; Costa, M. L.. (2015). Talassemia beta maior e gestação na adolescência: relato de dois casos. Revista Brasileira De Ginecologia E Obstetrícia, 37(6), 291–296. https://doi.org/10.1590/SO100-720320150005169Origa, R., amp; Comitini, F. (2019). Pregnancy in Thalassemia. Mediterranean journal of hematology and infectious diseases, 11(1), e2019019. https://doi.org/10.4084/MJHID.2019.019